AN INVESTIGATION OF SOME HEDGING STRATEGIES FOR CRUDE OIL MARKET - Andre Assis de Salles (International Journal of Energy Economics and Policy, 2013)
This paper examines the performance of bivariate volatility models for the crude oil spot and future returns of the WTI type barrel prices. Besides the volatility of spot and future crude oil barrel returns time series, the hedge ratio strategy is examined through the hedge effectiveness. Thus this study shows hedge strategies built using methodologies applied in the variance modelling of returns of crude oil prices in the spot and future markets, and covariance between these two market returns, which correspond to the inputs of the hedge strategy shown in this work. From the studied models the bivariate GARCH in a Diagonal VECH and BEKK representations was chosen, using three different models for the mean: a bivariate autoregressive, a vector autoregressive and a vector error correction. The methodologies used here take into consideration the denial of assumptions of homoscedasticity and normality for the return distributions making them more realistic.